1982
DOI: 10.1104/pp.70.4.1014
|View full text |Cite
|
Sign up to set email alerts
|

Site of Synthesis of NADPH

Abstract: The site of synthesis of the plastid membrane-located enzyme, protochlorophyllide reductase, has been determined. Plastid ribosome-deficient and normal rye (Secale cereake L., cv Rheidol) plants were grown in darkness at 33°C and 22°C, respectively. Extracts from these plants were analyzed for the levels of different ribosomal RNAs and cytochrome f and the activity of a number of enzymes with well-established sites of synthesis. The results confirmed that the higher temperature had induced a specific inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…From these results it has been concluded that the NADPH-protochlorophyllide oxidoreductase is synthesized on 80s ribosomes. Similar results have been obtained with other cereal plants [24]. They are consistent with our finding of a polyadenylated mRNA that codes for a high molecular weight precursor of the NADPH-protochlorophyllide oxidoreductase [lo].…”
Section: Resultssupporting
confidence: 93%
“…From these results it has been concluded that the NADPH-protochlorophyllide oxidoreductase is synthesized on 80s ribosomes. Similar results have been obtained with other cereal plants [24]. They are consistent with our finding of a polyadenylated mRNA that codes for a high molecular weight precursor of the NADPH-protochlorophyllide oxidoreductase [lo].…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, Cyt c oxidase activity exhibited a comparable level in extracts made from seedlings grown at 25 and 340C (Table I). The inhibition of RuBP carboxylase is readily explained by the fact that the synthesis of the large subunit coded by the plastid genome is prevented under the experimental conditions used, whereas that affecting NADPglyceraldehyde phosphate dehydrogenase could be tentatively correlated to the control exercised by the plastid on cytoplasmically synthetized polypeptides (5), as noted also in Secale (16, 19).…”
mentioning
confidence: 99%
“…Presently, concerning enzymes involved in the biogenesis of plastid terpenoids, the results obtained for phytoene synthetase are to be compared with those obtained for NADPH:Pchlide oxidoreductase (2,19), which is synthesized as a high mol wt precursor in the cytoplasm. Obviously, phytoene synthetase belongs to the family of plastidic stroma and membrane proteins made on 80S ribosomes and ultimately processed by posttranslational mechanisms (1 1,14,26).…”
mentioning
confidence: 99%